A experiência estética em Rilke revisitada a partir das interpretações de Gerd Bornheim - Aragao, Marina Pedreira (2020)
Based on two typescripts by the philosopher Gerd Bornheim, on Rainer Maria Rilke, we analyzed in this research the existing correlation between philosophy, poetry and aesthetics, tring to understand, more specifically, how plasticity and aesthetic experie